EFFECTS OF ETHYLENE GLYCOL AND KOH IN THE FORMATION OF 2-METHOXY-4-PROPYLPHENOL ON EUGENOL ISOMERIZATION REACTION - Muchalal Muchalal (Indonesian Journal of Chemistry, 2005)
Formation reaction mechanism of  2-methoxy-4-propylphenol on eugenol isomerization that involved protic hydrogen originated from ethylene glycol as a solvent has been done. To check this reaction mechanism, the effect of amounts of ethylene glycol as a solvent and KOH as a reagent on the quantity of 2-methoxy-4-propylphenol as a product has been carried out. The reaction product was analyzed by GC and GC-MS. Quantity of 2-methoxy-4-propylphenol as a product increased if ratio of quantity of ethylene glycol as solvent to quantity of KOH as reagent became larger. The result showed that formation process of 2-methoxy-4-propylphenol involved the protic hydrogen of solvent. The existence of cis-isoeugenol as an initiator compound in forming 2-methoxy-4-propylphenol indicated that the reaction mechanism followed the steps (1) cis-isoeugenolic ion gave Cb with negative charge at prophenyl group through resonance (2) a negative charge Cb then attacked a protic H atom in the solvent, and (3) hydride ion will attack Cb to form 2-methoxy-4-propylphenolic ion.